Corrections to “Frequency Limited & Weighted Model Reduction Algorithm With Error Bound: Application to Discrete-Time Doubly Fed Induction Generator Based Wind Turbines for Power System” - Sajid Bashir; Muhammad Imran; Sammana Batool; Muhammad Imran; Mian Ilyas Ahmad; Fahad Mumtaz Malik; Muhammad Salman; Abdul Wakeel; Usman Ali (IEEE Access)
In the above article [1], two relevant references [2], [3] were missing. The last sentence of Section I-C. should read “Proposed technique deals with frequency weighted and limited Gramians based MOR approach for the discrete-time systems. The frequency weighted version of proposed work appears in [2] while frequency limited work appears in [3] for continuous time systems. Compared to [2], [3], mathematical model and simulations in [1] are done for frequency weighted and limited scenarios for discrete time systems.”